Eukaryotic elongation factor 2 kinase promotes angiogenesis in hepatocellular carcinoma via PI3K/Akt and STAT3. Issue 5 (22nd July 2019) - Zhou, Ying; Li, Yaoting; Xu, Shihao; Lu, Jing; Zhu, Ziyi; Chen, Shaoli; Tan, Yuan; He, Peng; Xu, Jin; Proud, Christopher G.; Xie, Jianling; Shen, Kaikai
Abstract : Hepatocellular carcinoma (HCC) is an aggressive malignancy with increasing mortality in China. Angiogenesis is crucial for tumor formation, development and metastasis in HCC. Previous studies indicated that high expression levels of elongation factor 2 kinase (eEF2K), a protein kinase that negatively regulates the elongation stage of translation, were associated with poor prognosis of HCC. Here, we show that pharmacological inhibition or knockdown of eEF2K in highly metastatic liver cancer cells inhibits their colony forming and migratory capacities, as well as reducing their invasiveness. Importantly, knocking down eEF2K by lentiviral directed shRNA prevented tumor growth and angiogenesis of HCC in mice. Silencing of eEF2K in endothelial cells (HUVECs) led to a reduction in vascularization, evidenced by a decrease in capillary‐like structures in the matrigel. Notably, knocking down eEF2K reduced the expression of angiogenesis‐related growth factors in liver cancer cells and the expression of growth factor receptors on HUVECs, and thus restricted signaling crosstalk that promotes angiogenesis between HCC cells and endothelial cells. We also showed that silencing of eEF2K effectively reduced protein levels of SP1/KLF5 transcription factors and hence decreased the levels of bound SP1/KLF5 to the VEGF promoter, resulted in a decrease in VEGF mRNA expression. Knocking down eEF2K also led to a striking decrease in the phosphorylation of PI3K/Akt and STAT3, indicating inactivation of these tumorigenic pathways. Taken together, our data suggest that eEF2K contributes to angiogenesis and tumor progression in HCC via SP1/KLF5‐mediated VEGF expression, as well as the subsequent stimulation of PI3K/Akt and STAT3 signaling. Abstract : What's new? Eukaryotic elongation factor 2 kinase (eEF2K) represses protein synthesis by preventing ribosomes from moving along the mRNA strand. Recent work has associated eEF2K with tumor cell migration and invasion. These authors show how eEF2K promotes angiogenesis and tumor progression in hepatocellular cancer (HCC). Knocking down eEF2K in metastatic liver cancer cells reduced the cells' invasiveness. Cells without eEF2K had less SP1/KLF5 transcription factors, which reduced the amount of VEGF mRNA in the cell. The cells also showed less activity in the PI3K/Akt and STAT pathways. Reducing eEF2K expression in mice, they found, prevented HCC tumor growth and angiogenesis.